THE EFFECT STORYTELLING METHOD ON THE SPEAKING SKILL AND THE EMPATHY OF CHILDREN IN GROUP B KINDERGARTEN AL-KHAIRAAT PARIGI, PARIGI MOUTONG DISTRICT - Amrullah (Education Journal, 2021)
This study aimed to reveal the effect storytelling method on: (1) the speaking skill, (2) the empathy, and (3) the speaking skill and the empathy of children in Group B Kindergarten Al-Khairaat Parigi, Parigi Moutong District. This study was quasi-experimental research, targeting children in Group B Kindergarten Al-Khairaat Parigi, Parigi Moutong District. The research subject was 40 children, consisting of 20 children as the experimental group and 20 children as the control group. The research data were obtained from the observation at the time before and after the teaching. The data obtained were analyzed and tested by using the t-test and multivariate test. The results were as follows. First, there was a significant effect of the storytelling method on the speaking skill of the children in Group B Kindergarten Al-Khairaat Parigi, Parigi Moutong District at the significance level of 0.047 with the mean difference of 8.3. Second, there was a significant effect of the storytelling method on the empathy of children in Group B Kindergarten Al-Khairaat Parigi, Parigi Moutong District at the significance level of 0.016 with the mean difference of 7. Third, there was a significant effect of the storytelling method on the speaking skill and the empathy of the children in Group B Kindergarten Al-Khairaat Parigi, Parigi Moutong District at the significance level of 0.049.